Shape-tunable Pt–Ir alloy nanocatalysts with high performance in oxygen electrode reactions. Issue 3 (23rd December 2016) - Zhang, Tao; Li, Shuai-Chen; Zhu, Wei; Zhang, Zhi-Ping; Gu, Jun; Zhang, Ya-Wen
Abstract : Shape-tunable Pt–Ir alloy nanocatalysts were synthesized via a one-pot solvothermal method. The surface effects of Pt–Ir alloy nanocrystals deeply influenced the catalytic activity for oxygen electrode reactions. Abstract : For the first time, shape-tunable Pt–Ir alloy nanocatalysts including both single-crystalline (nano-octahedra (NOs), nano-truncated octahedra (NTOs), nanocubes (NCs)) and polycrystalline (nanocluster flowers (NCFs), nanowires (NWs), nano-short-chains (NSCs), and nano-octahedral stars (NOSs)) ones were synthesized with a facile one-pot solvothermal method, via precise control of the facet-selective agents (Br − and I − ). The surface effects of Pt–Ir alloy nanocatalysts for oxygen electrode reaction in acidic solution were intensively investigated. Pt–Ir alloy nanocatalysts showed enhanced catalytic activities for the oxygen evolution reaction (OER), which were 1.6 to 2.0 times those of the commercial Ir/C catalyst and the Pt/C–Ir/C mixture at an overpotential of 0.25 V. The catalytic activity for the OER exhibited a positive correlation with the proportion of surface IrO x species, but was restricted by the surface alloying effect. Besides the change of the intermediate adsorption state, the dissociation of water was also confirmed to be effective as the rate-determining step of the Pt–Ir alloy nanocatalysts. The catalytic activity for the oxygen reduction reaction (ORR) decreased with the increase of surface IrO x species. Pt–Ir nano-short-chains (NSCs) exhibited 1.3 times the catalytic activity as that of the commercial Pt/C catalyst at 0.80 V and 0.85 V, owing to the higher proportion of the (110) facets with irregular step sites exposed after the annealing treatment at 350 °C. The unique structure could prevent the mass transfer process from being obstructed by adsorbed bisulfate anions and oxidized species on the surfaces. Pt–Ir NSCs exhibited a catalytic efficiency of 46.7% and were considered to be a promising URFC catalyst.